2018
DOI: 10.1002/ccd.27799
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional printing assisted transcatheter closure of atrial septal defect with deficient posterior–inferior rim

Abstract: Objective: Though successful transcatheter closure has been reported in secundum atrial septal defect (ASD) with deficient posterior-inferior rim, it is still difficult to screen the appropriate candidates. Three-dimensional printing (3DP) makes in vitro trial occlusion possible, and might provide a feasible method in the prediction of successful closure.Methods: Thirty-five consecutive ASD patients (10M/25F, age, 47.7 AE 11.8 years) with deficient posterior-inferior rim (≤3 mm) were referred for attempted tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…13,26,27 For instance, Amedro et al reported an overall success rate of only 44% in an observational retrospective study, and Mathewson et al showed that device dislodgement had a significant impact on the pulmonary vein, inferior vena cava, and mitral valve. 12 In contrast, Chen et al 10 used minithoracotomy to effectively close the atrial septal defect with inferior vena cava rim deficiency, and Yan et al 28 used a 3D printing model to evaluate the feasibility of atrial septal defect closure before the procedure. According to the design of the double-disc occluder, the radius of the left and right discs differs by 2-3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…13,26,27 For instance, Amedro et al reported an overall success rate of only 44% in an observational retrospective study, and Mathewson et al showed that device dislodgement had a significant impact on the pulmonary vein, inferior vena cava, and mitral valve. 12 In contrast, Chen et al 10 used minithoracotomy to effectively close the atrial septal defect with inferior vena cava rim deficiency, and Yan et al 28 used a 3D printing model to evaluate the feasibility of atrial septal defect closure before the procedure. According to the design of the double-disc occluder, the radius of the left and right discs differs by 2-3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a high correlation between the ASD parameters measured from the 3D printed ASD models and the size parameters of intraoperative occluders, among which the circumference of 3D printed models resulted to be most relevant to the occluder device size. 3D printed ASD models can mimics the "en face" view for evaluating the morphological characteristics of an ASD comprehensively and provide reference for determine individualized plans in ASD occlusion 26 .…”
Section: Potential Applications Of Ultrasound-derived 3d Printed Asd Models In Asd Occlusionmentioning
confidence: 99%
“…Surprisingly, arterial and ventricular septal defects scored very low, between 2 and 5, although 3D printed models have been proven to be very useful in simulating closure procedures. Flexible models of septal defects can be used to perform mock transcatheter procedures and may help in choosing proper device size, improving the safety of surgery [14]. They help to understand spatial relationships between structures normally seen by cardiologists in echocardiography and learn how to proceed with the catheter delivery system.…”
Section: Clinical Example: Congenital Heart Disease and Transcatheter Interventionsmentioning
confidence: 99%